2002
DOI: 10.3354/meps227195
|View full text |Cite
|
Sign up to set email alerts
|

A GTT microsatellite repeat motif and differentiation between morphological forms of Littorina saxatilis: speciation in progress?

Abstract: A size (and sequence) variable microsatellite has been identified in the gastropod Littorina saxatilis following sequencing of products obtained through randomly amplified polymorphic DNA amplification. Size frequency distributions for this GTT repeat motif have been produced from a total of 439 L. saxatilis. Although there is evidence for a high prevalence of null alleles, consistent, largely significant, differences are found between the average size of this repeat in high shore, thin shelled morphs (L. saxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A total of 259 snails (20–22 individuals per sample) were genotyped for four L. saxatilis microsatellite loci: Lsax6CAA, Lx‐12 and Lx‐18 (Sokolov et al . 2002) and LsaxRAPDRPT1 (Wilding et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 259 snails (20–22 individuals per sample) were genotyped for four L. saxatilis microsatellite loci: Lsax6CAA, Lx‐12 and Lx‐18 (Sokolov et al . 2002) and LsaxRAPDRPT1 (Wilding et al . 2002).…”
Section: Methodsmentioning
confidence: 99%
“…There are additional examples of extreme and replicated tidal height variation at one marker relative to others in Littorina (Wilding et al 2002). A clear advantage of this genomic scan approach is that any marker linked to a potential target of selection could, in principle, be identified if the density of marker loci is sufficient.…”
Section: Genomic Scans For Intertidal Differentiationmentioning
confidence: 99%
“…It was considered that the reproductive barrier was likely to be only partial. Subsequent work has shown that shells conforming to the H and M morphotypes occur at sites widespread in the British Isles (Wilding et al 2002). Distinct pairs of morphs have also been described on shores in Sweden (Janson 1983) and Spain (Johannesson et al JOHN W. GRAHAME ET AL.…”
Section: Adaptation Environment and Gene Flowmentioning
confidence: 99%